Evolution - Monroe W Strickberger (Jones and Bartlett, 1995)
The book includes the historical development of evolutionary thought, cosmological and geological events, evolution of genetic systems and molecular pathways, and accounts of organisms from plants to humans. The book provides close to 450 figures, tables, and diagrams. It also includes boxed reviews of special topics, end-of-chapter summaries, lists of key terms, discussion questions, and a glossary